2019
DOI: 10.1101/644815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced Killing of Triple-Negative Breast Cancer Cells by Reassortant Reovirus and Topoisomerase Inhibitors

Abstract: 20Breast cancer is the second-leading cause of cancer-related deaths in women in the 21 United States. Triple-negative breast cancer constitutes a subset of breast cancer that is 22 Importance 38Patients afflicted by triple-negative breast cancer have decreased survival and limited 39 therapeutic options. Reovirus infection results in cell death of a variety of cancers, but it is 40 unknown if different reovirus types lead to triple-negative breast cancer cell death. In this study, 41 we generated two novel re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…2A). Similar to that observed previously (69), r2Reovirus impaired cell viability with faster kinetics than T1L and T3D did not impact cell viability. Treatment of cells with U0126 alone resulted in a dose-dependent cytostatic effect on cell viability, with cell viability leveling at 2 dpi when treated with 10 µM U0126 (red line).…”
Section: Results R2reovirus Impairs Mapk/erk Signalingsupporting
confidence: 88%
See 3 more Smart Citations
“…2A). Similar to that observed previously (69), r2Reovirus impaired cell viability with faster kinetics than T1L and T3D did not impact cell viability. Treatment of cells with U0126 alone resulted in a dose-dependent cytostatic effect on cell viability, with cell viability leveling at 2 dpi when treated with 10 µM U0126 (red line).…”
Section: Results R2reovirus Impairs Mapk/erk Signalingsupporting
confidence: 88%
“…We previously generated a reassortant reovirus with enhanced infective and cytotoxic properties in TNBC cells (69). The mechanisms through which this virus promotes TNBC cell death is not known.…”
Section: Results R2reovirus Impairs Mapk/erk Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Bourgeois-Daigneault et al have shown that the Maraba virus exerts an oncolytic effect against BrCa and the anti-tumor efficacy of the virus can be further enhanced by combination with paclitaxel or immune checkpoint inhibitors (ICIs) [61,62]. Also, NDV [63] and reovirus [64] have also shown oncolytic properties in preclinical models of BrCa.…”
Section: Replicating Viruses For Breast Cancer Therapymentioning
confidence: 99%